2018
DOI: 10.1007/s40618-018-0870-8
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of late-night salivary cortisol measured by automated electrochemiluminescence immunoassay for Cushing’s disease in an obese population

Abstract: In our obese cohort, we found that LNSC assayed by ECLIA had a low specificity in the diagnosis of CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Different groups have reported cut-off levels ranging from 2.8-12.3 nmol/l (0.10-0.45 μg/dl) with different sensitivities and specificities for the diagnosis of HC (▶ table 1) [8-12, 15-17,19-26]. Almost all cited studies used at least partially or solely healthy subjects as control group [8,12,16,17,[19][20][21][22][23]27]. This will very like-ly limit the use of the calculated cut-offs in daily clinical work because healthy subjects will not be undergoing HC testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different groups have reported cut-off levels ranging from 2.8-12.3 nmol/l (0.10-0.45 μg/dl) with different sensitivities and specificities for the diagnosis of HC (▶ table 1) [8-12, 15-17,19-26]. Almost all cited studies used at least partially or solely healthy subjects as control group [8,12,16,17,[19][20][21][22][23]27]. This will very like-ly limit the use of the calculated cut-offs in daily clinical work because healthy subjects will not be undergoing HC testing.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, published studies often included healthy controls or control groups that did not meet criteria for suspicion of HC to define thresholds (▶table 1). Described thresholds differ from 2.2-13.5 nmol/l (0.08-0.49 μg/dl) for the diagnosis of HC [9][10][11], with reported sensitivities and specificities of up to 100 % [9,10,[12][13][14][15][16][17]. Therefore, the goal of this prospective single centre study was to evaluate a cut-off value for LNSaC for the diagnosis of HC using a chemiluminescence immunoassay and to investigate the impact of different comorbidities and aetiologies on this cut-off in a tertiary endocrine referral centre with the so far largest meaningful control group.…”
Section: Introductionmentioning
confidence: 99%
“…Salivary cortisol is a reliable indicator of plasma free cortisol levels unrelated to the saliva production rate and CBG variability [71]. It has a high sensitivity but its specificity may be low, particularly in the elderly as well as in patients with comorbidities such as obesity, hypertension, and diabetes [57,60,72,73,74]. In healthy adults, advanced age has been reported to be associated with higher late-night salivary cortisol levels, with no evident influence of sex or BMI [75].…”
Section: Diagnosis and Differential Diagnosesmentioning
confidence: 99%
“…In healthy adults, advanced age has been reported to be associated with higher late-night salivary cortisol levels, with no evident influence of sex or BMI [75]. The proposed reference ranges and cut-off value of salivary cortisol differ immensely because of differences in the assays used [44,72]. It has also been reported that neither normal UFC levels nor normal late-night salivary cortisol levels exclude mild CS [76].…”
Section: Diagnosis and Differential Diagnosesmentioning
confidence: 99%
“…Data regarding sensitivity and sensibility of biochemical tests in obese populations are rather conflicting. Recently, sensitivity of the late-night salivary cortisol (LNSC) measured by automated electrochemiluminescence immunoassay (ECLIA) was found to be low in detecting CD in an obese population (BMI ≥ 35 kg/m 2 ) [49]. An automatic face classification of hypercortisolism by computer software has been even suggested as a novel screening approach in women [50].…”
Section: Advances In Diagnostic Testing and Need For New Testsmentioning
confidence: 99%